2016
DOI: 10.4329/wjr.v8.i11.868
|View full text |Cite
|
Sign up to set email alerts
|

Sonoelastography in the musculoskeletal system: Current role and future directions

Abstract: Ultrasound is an essential modality within musculoskeletal imaging, with the recent addition of elastography. The elastic properties of tissues are different from the acoustic impedance used to create B mode imaging and the flow properties used within Doppler imaging, hence elastography provides a different form of tissue assessment. The current role of ultrasound elastography in the musculoskeletal system will be reviewed, in particular with reference to muscles, tendons, ligaments, joints and soft tissue tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 58 publications
(48 reference statements)
0
62
0
Order By: Relevance
“…17,22 Soft Tissue Masses USE has been extensively explored in tumors outside the MSK system and was found useful in differentiating benign and malignant lesions mainly in the breast. 26 However, the value of USE in the differentiation of MSK tumors is not straightforward because a much greater variation in grade and histologic types occurs in sarcomas compared with breast lesions. [26][27][28][29] One of the early articles on this topic was a short pictorial essay by Lalitha et al They briefly reported that hemangiomas and neurofibromas demonstrate soft to firm consistency, typical of benign lesions (►Fig.…”
Section: Nervesmentioning
confidence: 99%
See 1 more Smart Citation
“…17,22 Soft Tissue Masses USE has been extensively explored in tumors outside the MSK system and was found useful in differentiating benign and malignant lesions mainly in the breast. 26 However, the value of USE in the differentiation of MSK tumors is not straightforward because a much greater variation in grade and histologic types occurs in sarcomas compared with breast lesions. [26][27][28][29] One of the early articles on this topic was a short pictorial essay by Lalitha et al They briefly reported that hemangiomas and neurofibromas demonstrate soft to firm consistency, typical of benign lesions (►Fig.…”
Section: Nervesmentioning
confidence: 99%
“…accessibility, susceptibility to pathology, and relatively large size. 26 Two other important sites in USE tendon research are the rotator cuff and the common extensor and flexor tendons of the elbow. [52][53][54] In Achilles tendinopathy evaluation, the studies showed moderate to perfect correlation between the USE and Bmode US and excellent correlation with functional scores.…”
Section: Tendonmentioning
confidence: 99%
“…Ultrasound (US) elastography measures tissue elasticity by using high‐frequency sound waves to assess static or dynamic deformation behavior of tissue after a stimulus is applied 1 . This technique has been described most commonly in the context of isotropic tissues, such as the liver, and in neoplastic diseases 2 but is now becoming of more interest in anisotropic tissues, such as those in the musculoskeletal system 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…[18] Shear wave elastography (SWE) is a non-invasive and dynamic method of quantifying changes in tendon elasticity, involving application of a focused ultrasound pulse to the tissue being imaged. [19][20][21] SWE is a type of US elastography that uses shear waves generated by a remote radiation force of focused ultrasonic beams to assess tissue elasticity. It measures the velocity of shear waves (in metres per second) moving through tissue, and displays these in a quantitative manner via a real-time elastogram, in which elasticity is portrayed as a colour-coded representation over a B-mode image.…”
Section: Introductionmentioning
confidence: 99%